Characterization of Fish Gelatin Obtained from Atlantic Cod Skin Using Enzymatic Treatment - Svetlana R. Derkach; Daria S. Kolotova; Yuliya A. Kuchina; Nadezhda V. Shumskaya (Polymers, 2022)
In recent years, there has been increased interest in the production of gelatin from alternative sources, such as raw fish materials. Traditionally, gelatin is obtained using an acidic or alkaline treatment. However, these methods have some disadvantages, such as the long times for processing raw materials and the use of large amounts of water and chemicals. Furthermore, milder processing regimes are required for producing fish gelatin. Enzymes could be the solution for improving the technology of fish gelatin production, due to their specificity and ability to increase the rate of collagen digestion. In this work, samples of gelatin from cod skin were obtained using enzymes of bacterial (protosubtilin) and animal (pancreatin) origins. The use of enzymes reduced the duration of extraction by 40%, and the yield of the final product was increased from 51% to 58–60%. The dependence of the contents of the main components of the secondary structure of gelatin and its rheological and thermal properties on molecular weight was also established. In this study, the gelatins obtained without enzymes and with protosubtilin were shown to have the most desirable characteristics, namely of the highest molecular weights and the highest proportion of ordered structures.